Use of drug treatment for secondary prevention of cardiovascular disease in urban and rural communities of China: China Kadoorie Biobank Study of 0.5 million people - Chen, Y; Li, L; Zhang, Q; Clarke, R; Chen, J; Guo, Y; Bian, Z; Pan, X; Peto, R; Tao, R; Shi, K; Collins, R; et al. (Elsevier, 2014)
Aims Relatively little is known about the use of medication for the secondary prevention of cardiovascular disease (CVD) events in China, and the relevance to it of socioeconomic, lifestyle and health-related factors. Methods and results We analysed cross-sectional data from the China Kadoorie Biobank (CKB) of 512,891 adults aged 30-79 years recruited from 1737 rural and urban communities in China. Information about doctor-diagnosed ischaemic heart disease (IHD) and stroke, and the use of medication for the secondary prevention of CVD events, were recorded by interview. Multivariate logistic regression was used to estimate odds ratios (ORs) for use of secondary preventive treatment, adjusting simultaneously for age, sex, area and education. Overall, 23,129 (4.5%) participants reported a history of CVD (3.0% IHD, 1.7% stroke). Among them, 35% reported current use of any of 6 classes of drug (anti-platelet, statins, diuretics, ACE-I, β-blockers or calcium-channel blockers) for the prevention of CVD events, with the rate of usage greater in those with older age, higher levels of income, education, BMI or blood pressure. The use of these agents was associated positively with history of diagnosed hypertension (OR 7.5; 95% confidence intervals: 7.08-8.06) and diabetes (1.40; 1.28-1.52) and inversely with self-rated health status, but there was no association with years since diagnosis. Conclusions Despite recent improvements in hospital care in China, only one in three individuals with prior CVD was routinely treated with any proven secondary preventive drugs. The treatment rates were correlated with the existence of other risk factors, in particular evidence of hypertension. © 2013 Elsevier Ireland Ltd.